Influence of Using CANVA Media on Learning Outcomes of ClassVII Students at MTSN 2 Sidenreng Rappang - Megawati Nur, Dian; Hasanuddin; Sam Hermansyah (Global Synthesis in Education Journal, 2023)
The lack of excitement for training students' speaking abilities is at the root of the problem in this study. Researchers are curious about: 1) This English Tutor exercise provides an incentive for students to practice speaking English. 2) Students' conduct or effort in practicing speaking English through English Tutor activities, attitudes, interests, values, or desires The design of this study is descriptive-quantitative. Creswell (2012: 13) describes quantitative research as defining a research challenge based on trends in the field or the need to explain why something occurs. According to the study's findings, 1) the learner's effort in practicing speaking English among ILP students is 63% or higher, and 2) the students'' interest in practicing speaking English is 37%. 3) 47% of learners have a positive attitude regarding English-speaking practice. 4) The student has a 50% motivation to practice speaking English. The following are the findings: 1) Having a variety of learning activities and subjects available is beneficial for increasing motivation and offering opportunity for concept exploration. 2) To avoid monotony, vary the tactics employed in the learning process. 3) Rewarding and encouraging students who can successfully express themselves in English. 4) Making the classroom an inviting atmosphere.